CIVIL MILITARY COORDINATION IN HUMANITARIAN ACTIVITIES (Annual of the Faculty of Philosophy in Skopje, 2019)
Military co-ordination in recent decades faces a number of complex and ofteninterconnected challenges, including increased international interventions in fragileand conflict-affected states, the rise in frequency and scale of natural disasters, andthe rapid proliferation of "humanitarian" actors, including non-governmental organizations,non-profit organizations and the private sector. Debates on civil-militarycoordination tend to focus on conceptual issues, with lack of analysis as to how therelationship works at a practical level and more importantly how this relationshipaffects the humanitarian outcome for the population in need of humanitarian aid andprotection. In the research of civil-military coordination, the author is guided by thefollowing questions: How can humanitarian and military actors engage more effectivelyand strategically with one another? What can they really expect from eachother? Are the existing frameworks for civil-military coordination (at the political,strategic and operational level) sufficient and appropriate for the goal? Answers ofthese questions would be an important step in securing a more constructive and effectivecivil-military relationship at strategic, operational and tactical levels.
Keywords: CIVIL-MILITARY COORDINATION; COOPERATION; SUPPORT; PRINCIPLES; LAST RESORT